PERAN PASAR UANG SYARIAH DALAM MENJAGA KESEIMBANGAN PASAR DI INDONESIA - Fifi Afista; Dina Aslamiya Anjalina; Farah Berliana; Gunawan Aji (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
The Islamic money market, as an integral part of the Indonesian financial system, plays a crucial role in maintaining market balance in Indonesia. This research investigates the role of the Islamic money market in maintaining market balance in Indonesia by outlining the contribution of the Islamic money market to Indonesia's economic stability through efficient fund allocation mechanisms and fairer risk distribution in accordance with sharia principles. The policy regarding the sharia money market in Indonesia is based on Bank Indonesia Regulation Number: 10/36/PBI/2008 dated 10 December 2008 concerning Sharia Monetary Operations as well as the national sharia council fatwa, namely No.37/DSN-MUI/X/2002 concerning the prohibition on the use of interest. on the Islamic money market. The Islamic money market also plays a role in increasing financial access for people who were previously not served by the conventional financial system and plays a role in reducing market volatility and overcoming economic instability by providing sustainable and trustworthy financial solutions in accordance with sharia principles. Thus, the Islamic money market not only functions as a place to carry out financial transactions, but also as the main pillar in maintaining market balance and strengthening the foundation of the Indonesian economy as a whole. This research uses a qualitative method with a literature study approach, where this research produces descriptive data. The findings of this research provide insight into the history of financial markets, we can take wise steps to ensure fairness, stability and sustainability of the economy based on sharia principles.